1984
DOI: 10.1063/1.447434
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the conformational barriers to internal rotation of 3-fluoropropene from far infrared and low frequency Raman spectra

Abstract: The far infrared (200–40 cm−1) and low frequency Raman (1000–20 cm−1) spectra of gaseous 3-fluoropropene have been recorded. The fundamental asymmetric torsion for the conformer which has the fluorine atom cis to the double bond has been observed at 164.62 cm−1 with four excited states falling at lower frequencies, and the corresponding fundamental torsion of the gauche conformer was observed at 108.00 cm−1 with three excited states observed at lower frequencies. From these data the potential function for inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
3

Year Published

1985
1985
1996
1996

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 26 publications
3
28
3
Order By: Relevance
“…The preference of an in-plane C-F bond is possibly related to an electrostatic preference, the Ct--Fdipole lying near the ortho C-Ht dipole (calculated net charges on fluorine and the ortho hydrogen are +0.06 and -0.15 in units of electron charge for 1). An analogous eclipsing conformation is found to be most stable in 3-fluoropropene (8).…”
Section: Introductionmentioning
confidence: 82%
“…The preference of an in-plane C-F bond is possibly related to an electrostatic preference, the Ct--Fdipole lying near the ortho C-Ht dipole (calculated net charges on fluorine and the ortho hydrogen are +0.06 and -0.15 in units of electron charge for 1). An analogous eclipsing conformation is found to be most stable in 3-fluoropropene (8).…”
Section: Introductionmentioning
confidence: 82%
“…The force field in Cartesian coordinates was calculated by the GAUSSIAN-90 program (38) with the RHF/3-21G" basis set. From previous studies (24), it was found that the differences in the values of force constants and frequencies are not significant when the smaller, as opposed to the larger, RHF/ 6-31G* basis set is used. These calculations were performed by using the Wilson FG matrix method (40).…”
Section: Normal Coorditzate Analysismentioning
confidence: 99%
“…Our recent investigation~ have included the determination of the potential functions governing internal rotation about the ~( s p~) -~( s p ' ) bonds of the parent 3-halopropenes and some substituted derivatives (24)(25)(26)(27)(28)(29)(30)(31)(32). Ally1 fluoride (24)(25)(26), chloride (27), bromide (28,31), and iodide (32) have been determined to exist as a mixture of syn and gauche conformers, and for the fluoride we have shown that the conformer that has the halogen atom syn to the double bond is the more stable rotamer (24)(25)(26). For 3-chloropropene, the value of the energy difference (27) was inferred to be less than 100 cm-' (286 cal/mol) and the spectral data merely indicated a very slight preference for the syn conformer for the gaseous state.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have been of interest for a number of years, since allyl fluoride [1][2][3][4] has its more stable conformer as the cis (synclinal) rotamer, whereas the other allyl halides [5][6][7][8][9] have the gauche (anticlinal) form as the most stable conformer in the fluid phases. For allyl fluoride, the most stable conformer in the solid is the cis rotamer, whereas the other conformers have the gauche rotamer as the more stable conformer in the solid.…”
Section: Introductionmentioning
confidence: 99%
“…For some time we have been investigating the relative stability of the rotamers of the allyl halides [1][2][3][4][5][6][7][8][9], along with the methyl [10][11][12][13] and halo [14,15] substituted molecules. These compounds have been of interest for a number of years, since allyl fluoride [1][2][3][4] has its more stable conformer as the cis (synclinal) rotamer, whereas the other allyl halides [5][6][7][8][9] have the gauche (anticlinal) form as the most stable conformer in the fluid phases.…”
Section: Introductionmentioning
confidence: 99%